Grammatical Cohesive Devices in Taylor Swift’s Nyu 2022 Commencement Speech - Ni Luh Putu Yurikayani; I Gusti Ayu Gede Sosiowati; Anak Agung Sagung Shanti Sari Dewi (VISA: Journal of Vision and Ideas, 2024)
This study revolves around the study of discourse, specifically concerning the role of grammatical cohesive devices in spoken discourse namely speech. This study applied Halliday and Hasan’s theory of cohesion (1976). This study aims at identifying the types of grammatical cohesive devices used and analyzing the functions of each grammatical cohesive devices in the speech. The data of this study was taken from the Taylor Swift’s NYU 2022 commencement speech. The method applies in this study is descriptive quantitative method. In collecting the data, documentation method and note-taking technique were used. The grammatical cohesive devices based on Halliday and Hasan (1976) theory consist of reference, substitution, ellipsis, and conjunction. The method for presenting the data analysis in this study used informal method by using descriptive qualitative method and content analysis technique. The finding shows that almost all types of grammatical cohesive devices are found in Taylor Swift’s NYU 2022 commencement speech. The types are reference, substitution, ellipsis, and conjunction. Based on the analysis, the most dominant type appeared in the speech is reference and the less frequently appeared is substitution. The result also shows how each type of grammatical cohesive devices functions in the speech. The functions of grammatical cohesive devices are important to create cohesion, clarity, and to make the listener understand the implied meaning made by the speaker.